Link between metacognition and social cognition in schizophrenia: a systematic review and meta-analysis - Motut, Alex; Isaac, Clémence; Castillo, Marie-Carmen; Januel, Dominique (Frontiers in Psychiatry, 2023)
Introduction: Metacognition is the ability to reflect on one's own cognitive processes, monitor and regulate them to enhance mental performance. Social cognition involves the capacity to perceive and respond to social cues from others. The study of metacognition and social cognition is an expanding research field in psychiatry. Both domains are related to neurocognition, symptoms and psychosocial functioning in schizophrenia. Understanding the relationship between social cognition and metacognition may be pivotal for enhancing the treatment of cognitive symptoms in schizophrenia. Method: We conducted a PRISMA systematic review and meta-analysis on quantitative studies comparing metacognition to social cognitive outcomes in adult outpatients with a schizophrenia spectrum disorder. Reports were retrieved from the Medline, ScienceDirect and PsycINFO databases up to July 13th, 2023. Risk of bias was assessed with the Cochrane tool. Results: Our review included 1,036 participants across 17 reports, with 12 reports included in the meta-analysis. We found a significant positive correlation (r = .28, 95% CI: [.14, .41]) between social cognition and metacognition. Subgroup analyses indicated that metacognition was specifically associated with theory of mind, attribution, and emotion processing. Different patterns of correlations were observed according to the assessment of metacognition and its subdimensions. Conclusion: Despite discrepancies among the included studies, no publication bias was detected. The results suggest that metacognition and social cognition are distinct but related constructs. Those processes should be assessed and treated together, along with neurocognition, in schizophrenia.